2019
DOI: 10.3390/app10010183
|View full text |Cite
|
Sign up to set email alerts
|

Laser Finishing of Ti6Al4V Additive Manufactured Parts by Electron Beam Melting

Abstract: In this work, the feasibility of laser surface finishing of parts obtained by additive manufacturing (AM) was investigated. To this end, a 450 W fiber laser (operating in continuous wave, CW) was adopted to treat the surface of Ti-6Al-4V samples obtained via electron beam melting (EBM). During the tests, different laser energy densities and scanning speeds were used. In order to assess the quality of the treatment, either the as-built or the treated samples were analyzed by means of a three-dimensional (3D) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…At the lower focal distance (Fd = 5 mm) the amount of energy transferred to the material is enough to vaporize the higher peaks and melt the greater ones. Conversely, at a higher focal distance (Fd = 7.5 mm), the energy available to the machining is lower and the higher peaks are just melted, leaving some irregularity as explained in [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the lower focal distance (Fd = 5 mm) the amount of energy transferred to the material is enough to vaporize the higher peaks and melt the greater ones. Conversely, at a higher focal distance (Fd = 7.5 mm), the energy available to the machining is lower and the higher peaks are just melted, leaving some irregularity as explained in [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…A pre-heated process chamber and high melting capacity of the EBM system avoid the arising of residual stresses and martensitic structures in the printed parts [ 30 ]. For further details on the printing procedure, reference is made to a previous work dedicated to finishing of additively manufactured Ti6Al4V parts [ 28 , 29 ]. EBM samples were built with an axial-symmetric geometry ( Figure 1 ) typical of fatigue test specimens, in order to systematically investigate the influence of AFB and LF treatments on the fatigue life of parts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As surface finish has been established as a significant parameter affecting as-built AM material properties, an increased interest has grown in the literature exploring the effects of EBM processing parameters on surface roughness 29 – 31 . A rough surface and insufficient surface quality can also be improved by different post-process surface finishing methods such as mechanical (sandblasting 32 , abrasive blasting 27 ), chemical (acid etching 33 , oxidation), electrochemical (passivation, electropolishing 34 ), thermal processes (micro-arc oxidation 35 ), and laser treatment 36 . Some authors reported the application of the laser surface treatment technique for AM-produced parts without detachment from the build plate 37 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Some authors reported the application of the laser surface treatment technique for AM-produced parts without detachment from the build plate 37 39 . However, ex-situ laser treatment was studied as an effective method to decrease the surface roughness of the EBM parts by 80% 36 . On the other hand, laser surface remelting (LSR) was reported as an effective in-situ method to enhance the surface roughness of SLM-produced parts 37 39 .…”
Section: Introductionmentioning
confidence: 99%